Development of high frequency Tan Delta measurement method for 132kV transmission underground cables - Chakrabarty C.K.; Avinash A.R.; Ahmad Basri A.G.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Capacitance; Phase shift; Underground cables; Dissipation factors; High frequency HF; HVAC; Tangent delta; XLPE; Cables